Ireland : an Oxford archaeological guide to sites from earliest times to AD 1600 - Halpin, Andrew (Oxford archaeological guides., 2006)
Ireland is a country rich in archaeological sites. "Ireland: An Oxford Archaeological Guide" provides the ultimate handbook to this fascinating heritage. Covering the entire island of Ireland, from Antrim to Wexford, Dublin to Sligo, the book contains over 250 plans and illustrations of Ireland's major archaeological treasures and covers sites dating from the time of the first settlers in prehistoric times right up to the seventeenth century. The book opens with a useful introduction to the history of Ireland, setting the archaeological material in its wider historical context, and then takes the reader on an unparalleled journey through the major sites and places of interest. Each chapter focuses on a particular geographical region and is introduced by a useful survey of the history and geography of the region in question. This is followed by detailed descriptions of the major archaeological sites within each region, arranged alphabetically and including travel directions, historical overview of the site, and details of the site's major features and the latest available archaeological evidence.; As the most comprehensive and detailed compact guide to the archaeological sites of Ireland, this new volume will prove invaluable to archaeologists, students of Irish history, and tourists alike.